FROM SCRIPT TO SPEECH: THE INTERPLAY BETWEEN WRITTEN AND ORAL TRADITIONS IN PHILOLOGICAL STUDIES - Khilola Ismoilova; Robiya Ismonaliyeva; Mohlaroy Qodirova (TADQIQOTLAR, 2025)
The dynamic relationship between written and oral traditions has long intrigued philologists, as both forms of expression reveal the evolution of human language, culture, and cognition. This study examines the interplay between script and speech within philological research, highlighting how oral traditions influence written texts and how literacy transforms oral expression. Drawing from classical, medieval, and indigenous linguistic traditions, the article explores how oral performance, memorization, and storytelling shaped the transmission of texts before and after the advent of writing. The research also addresses how modern philology, supported by linguistic anthropology and digital humanities, redefines the boundaries between oral and written forms. Case studies from Homeric epics, Old English poetry, and African oral literature demonstrate that script and speech are not opposing systems but complementary forces in cultural preservation. The paper concludes that philological inquiry into both forms deepens our understanding of linguistic creativity and cultural continuity.